Contribution Of Pesantren Through Collective Leadership From A Total Quality Management Perspective - Basit, Abdul; Irfan, Ahmad; Rayhan, Ahmad (Universitas Muhammadiyah Tangerang, 2025)
This study aims to examine the extent to which the quality of management at Darunnajah Islamic Boarding School in Ulujami has improved through the implementation of collective leadership. The research begins by observing Darunnajah as a community-based pesantren established in Jakarta, Indonesia. Today, Darunnajah students have achieved both national and international recognition in the fields of religious studies, applied sciences, and vocational skills. The study then focuses on the leadership’s commitment to enhancing the quality management of the pesantren from the perspective of Edward Sallis's Total Quality Management (TQM), particularly in relation to the three main educational components: students, educators, and educational staff. This research employs a qualitative approach. Data collection was carried out through two methods. First, primary data were obtained through initial and follow-up field observations, as well as structured and unstructured interviews. Second, secondary data were collected from documents, alumni input, seminars, relevant literature, electronic media, and academic materials. The validity of the data was ensured through prolonged engagement in the field and triangulation. The results of the study indicate that collective leadership at Darunnajah Islamic Boarding School has had a positive impact on various aspects. The teaching and learning process has improved through better educator qualifications, satisfactory staff performance, and well-maintained facilities and infrastructure, which has also contributed to an increase in student enrollment. Internally, institutional development is reflected in the establishment of laboratories, canteens and cooperatives, sports facilities, and enhanced student skills. Externally, the pesantren has strengthened cooperation with local governments and companies, served as a role model for other Islamic boarding schools, and attracted attention from researchers and foreign education experts